A novel anti-collision protocol for optimization of remote sensing in dense reader network - Nawaz, F. (Springer Verlag, 2015)
Passive Radio Frequency Identification (RFID) network with several reader placed densely and close to each other are susceptible to reader collision problem. In this paper, a novel and efficient RFID readerâs anti-collision protocol is proposed based on Neighbor Friendly Reader Anti-collision (NFRA) mechanism by revising its contention procedure to provide higher throughput in dense reader network. The behavior of the algorithm is evaluated through a set of simulation experiments which demonstrates that the algorithm is 15 efficient than NFRA. It also has higher fairness as compared to NFRA and other state-of-the-art proposals. Â© Springer International Publishing Switzerland 2015.